Genetic variability in the microRNA binding sites of BMPR1B, TGFBR1, IQGAP1, KRAS, SETD8 and RYR3 and risk of breast cancer in Colombian women - Garcia Mesa, Karen; Lorenzo Bermejo, Justo; Torres, Diana; Gilbert, Michael; Plass, Christoph; Hamann, Ute (OncoTargets and therapy, 2020)
Genetic Variability in the microRNA Binding Sites of BMPR1B, TGFBR1, IQGAP1, KRAS, SETD8 and RYR3 and Risk of Breast Cancer in Colombian Women
Gesehen am 11.02.2022